Export and Economic Growth in Saudi Arabia: The Granger Causality Test - Alhakimi, Saif Sallam (Asian Journal of Economics and Empirical Research, 2018)
An export-led growth strategy aims to encourage producers to export their goods through various economic and governmental policies. This study was carried out with the primary objective of investigating the relationship between exports and economic growth in the Kingdom of Saudi Arabia (hereafter referred to as the KSA), specifically by examining the causality between exports and KSA’s economic growth. There are four main propositions for the relationship between exports and economic growth: export-led growth (ELG), growth-driven exports (GDE), and feedback relationships between exports and economic growth. To complete this study, samples were used based on 37 years of annual data. The study also employed a unit root test, a co-integration test, and the Granger causality test to observe the causal relationship between exports and economic growth. Data were collected for exports, which were expressed according to export growth. Economic growth, meanwhile, was measured according to gross domestic product (GDP) per capita and expressed in terms of US dollars. The result of this study found that GDP per capita significantly influenced exports, while exports did not affect GDP.